2015
DOI: 10.1177/1932296815593295
|View full text |Cite
|
Sign up to set email alerts
|

Usability of the Novel Liraglutide 3.0 mg Pen Injector Among Overweight or Obese Adult Patients With or Without Prior Injection Experience

Abstract: Obesity is a chronic disease often encompassed by a multitude of serious comorbidities, making its prevention and treatment public health priorities. Globally, by 2030, the numbers of adults who are overweight ( It has been shown that an increase in BMI is directly correlated with a reduction in life expectancy and increase in obesity-related comorbidities such as type 2 diabetes mellitus (T2DM).3-5 A 5-10% weight loss can provide clinically relevant improvements in obesity-related comorbidities and quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Several prominent associations, including the Canadian Medical Association, recognize obesity as a chronic relapsing primary disease characterized by excessive accumulation and storage of fat in the body . Obesity is associated with many serious comorbidities, including hypertension, type 2 diabetes (T2D), cardiovascular disease, osteoarthritis, and certain types of cancer . The continued rise in the prevalence of obesity makes prevention and treatment public health priorities because it has been shown that an increase in BMI is correlated with a reduction of life expectancy and with an increase of obesity‐related comorbidities .…”
Section: Introductionmentioning
confidence: 99%
“…Several prominent associations, including the Canadian Medical Association, recognize obesity as a chronic relapsing primary disease characterized by excessive accumulation and storage of fat in the body . Obesity is associated with many serious comorbidities, including hypertension, type 2 diabetes (T2D), cardiovascular disease, osteoarthritis, and certain types of cancer . The continued rise in the prevalence of obesity makes prevention and treatment public health priorities because it has been shown that an increase in BMI is correlated with a reduction of life expectancy and with an increase of obesity‐related comorbidities .…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, some users were not aware that they had to activate the device by pushing a button (Robinson et al, 2014;Salter et al, 2014;Brown et al, 2013). Secondly, some users were not able to push the button with enough force to trigger the injection (Fujioka et al, 2015;Callis Duffin et al, 2016;Matfin et al, 2015;Demary et al, 2014). The same distinction could be made for devices that have to be activated by pressing them against the body.…”
Section: Categories Of Identified Use Errors and Close Callsmentioning
confidence: 99%
“…This includes physical characteristics (hand size, mobility, flexibility, strength, etc. ), sensory performance and cognitive abilities (Fujioka et al, 2015;Food and Drug Administration, 2017). The application of information about human capabilities and limitations to device design in order to optimize a device's performance and safety is known as human factors engineering or usability engineering (Lange et al, 2015;Russ et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations